PENGEMBANGAN LKPD BERBASIS LEARNING CYCLE 5 E SUBTEMA SUHU DAN KALOR UNTUK SISWA KELAS V SDN 66 PEKANBARU - Susana; Zaka Hadi Ramadan (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2022)
The purpose of this research is to produce student worksheets based on learning cycle 5e sub-theme of temperature and heat for fifth grade elementary school students. This research was carried out using a formative research type method, development research focused on two stages, namely preliminary and formative evaluation which included self evaluation, prototyping (expert reviews, one-to-one and small group), and field tests. However, this study focused on the preliminary stage and the formative evaluation stage which included self evaluation, proto typing (expert reviews). Collecting data using observation, interviews and questionnaires. Based on assessments by materials experts, linguists and design experts obtained the results of 93,184% with a valid category. The overall percentage is obtained based on material validation 88,125% with valid category, language validation 95% with valid category, and design validation 96,428% with valid category.